Implementation of STEM-PjBL-Based E-Module on the Circulatory System for Improving Critical Thinking Skills and Science Process Skills of High School Students - Nurul Jannah; Yustina Yustina; Sri Wulandari (FKIP - Universitas Riau, 2026)
Twenty-first century education requires the integration of technology to support the development of students’ critical thinking skills and science process skills. However, these skills remain low, particularly in understanding abstract topics such as the circulatory system. This study aimed to investigate the effect of a STEM-PjBL-based e-module on students’ critical thinking skills and science process skills. The novelty of this study lies in the implementation of an e-module that integrates STEM concepts, STEM-PjBL learning stages, and contextual project activities to simultaneously support the development of both skills. A quasi-experimental method with a pretest-posttest control group design was employed involving Grade XI students at SMA Sains Tahfizh Islamic Center. Data were collected using critical thinking tests and science process skills observation sheets and analyzed using MANOVA. The results showed that the STEM-PjBL-based e-module significantly affected students’ critical thinking skills (p = 0.001, partial η² = 0.206) and science process skills (p < 0.001, partial η² = 0.490). These findings indicate that the STEM-PjBL-based e-module provides substantial support for developing students’ critical thinking skills and science process skills through contextual and meaningful learning experiences.